AB1129 ULTRASOUND MEASUREMENT OF MUSCLE THICKNESS AT THE PROXIMAL FOREARM: VALIDITY ISSUES. (June 2019) - Castell, Sonia; Smerilli, Gianluca; Cipolletta, Edoardo; Salaffi, Fausto; Filippucci, Emilio; Grassi, Walter
Abstract : Background: The term sarcopenia defines the muscle strenght loss and muscle mass loss due to aging, and it is one out of three criteria for the diagnose of frailty in the elderly. A number of studies have related the handgrip strength with muscle thickness (MT) in the forearm measured by ultrasound (US) 1, but a standardized scanning protocol has not been described and its interobserver reliability has not been investigated yet. Objectives: The aims of this study were to provide detailed description of the scanning protocol to measure the MT in the forearm and to test its feasibility and interobserver reliability. Methods: A total of 27 consecutive subjects were enrolled at Ospedale "Carlo Urbani", in Jesi (Ancona, Italy): 2 healthy volunteers recruited from among our staff, and 25 patients referred to the Rheumatology Department affected by rheumatoid arthritis (5), psoriatic arthritis (4), spondyloarthritis (3), polymyalgia rheumatica (2), systemic lupus erythematosus (1), systemic sclerosis (1), overlap SLE/SSc (1), Sjögren syndrome (1), antisynthetase syndrome (1), undifferentiated connective tissue disease (1), osteoporosis (1), small vessels vasculitides (2) and fibromyalgia (2). The female to male ratio was 19/27, the mean age was 52.1 years (SD ±13.7), and the mean Body Mass Index was 27.4 Kg/m 2 (SD ±4.2). Four rheumatologists (SC, EC, GS, EF) trained in musculoeskeletal US, with a different degree of experience, performed the examinations using a MyLab ClassC (Esaote SpA) equipped with a broadband linear probe (frequency range 4-13 MHz). All subjects sat in front of the sonographer with their hands supinated and the forearm resting on the examining table. First, the coronoid process was imaged according to the "longitudinal scan of the coronoid recess" as indicated by the 2017 EULAR US guidelines. Then the probe was moved distally following bony cortex until the ulnar tuberosity was identified. Immediately distally to the ulnar tuberosity the bone turns flat and hyperechoic and this was taken as the anatomical reference for the measurement. Afterwards the probe orientation was changed to obtain a transverse view. During the rotation, the proximal third of the diaphysis of the radius was imaged. Two MT were measured, the ulnar MT (UMT) and the radial MT (RMT), between the subcutaneous tissue-muscle interface and the muscle-bone interface of each bone respectively. The measurement of UMT and RMT of both arms were registered, as well as the scanning time of all the examiners. Results: We found an excellent interobserver reliability of this scanning protocol, with and interclass correlation coefficient (ICC) among the four sonographers of 0.975 (CI 0.955 - 0.987) for the right UMT, an ICC of 0.968 (CI 0.942 - 0.984) for the left UMT, an ICC of 0.932 (CI 0.878 - 0.966) for the right RMT and an ICC of 0.949 (CI 0.908 - 0.974) for the left RMT. The mean time required to acquire all measurements in each subject was less than five minutes (SC 4.4 min; EC 4 min; GS 4.2 min; EF 4.5 min). Conclusion: The results of this study provide evidence in favour of both feasibility and interoberver reliability of US measurement of the forearm MT. References: [1] Abe T, Thiebaus R S, Loenneke J P, Ogawa M and Mitsukawa N. Association between forearm muscle thickness and age-related loss of skeletal muscle mass, handgrip and knee extension strength and walking performance in old men and women: a pilot study. Ultrasound in Med. & Biol., Vol. 40, No. 9, pp 2069-2075, 2014. Disclosure of Interests: Sonia Castell: None declared, Gianluca Smerilli: None declared, Edoardo Cipolletta: None declared, Fausto Salaffi Grant/research support from: Abbvie, Roche, Novartis, BMS, Pfizer, Sanofi, Speakers bureau: Abbvie, Roche, Novartis, Pfizer, Sanofi, BMS, Emilio Filippucci: None declared, Walter Grassi: None declared